A Study of Chaharbagh Avenue as a Case Study to Improve Access for War-invalids and Physical Disabled People - F. majidi; S. teimouri (Afarand Scholarly Publishing Institute, 2011)
During a day, citizens pass through different pats and sometimes face an accident and be injured by it. Meanwhile war invalids and disabled people suffering from inappropriate designs, experience such situation more because of their disabilities. Considering the definition of disability as any limitation or impairment of sensorimotor system causing deficiency in motion or participation with others, and of the physically disabled as people who have physical impairments or weaknesses by any reason, and who have to use mobility aids, this article presented to clarify the features of appropriate paths for war invalids and disabled people, also take their problems as vulnerable groups in society into account. The aim of this study was to confirm the necessity to design appropriate paths, and to identify improvements required to bring available paths up to standards for disabled. In this regard, the problems of disabled people investigated, and after that some standards to design safe paths presented. In practice, it is conducted a field research on chaharbagh abasi avenue as a main and busy one in Isfahan, in order to find the physical disabled problems. Resulting in the form of proposals is presented in most tables.